Elitism and the Approach to God - Raybould, Robin (Brill's Studies in Intellectual History, 2025)
Elitism and the Approach to God investigates a historical and cultural dichotomy in European history which has not hitherto been satisfactorily explained Why did so many of the most influential "authorities" of the age insist that the nature and mystery of the divine and of God should not be shared with "the vulgar crowd", that is with the ordinary people, although this appears to be the principal purpose of all other religious teaching throughout the period? Robin Raybould gives examples from the works of more than sixty "authorities" who insisted that the mysteries of the divine should remain secret. He then surveys the attempts of other religious and civic leaders, both pagan and Christian, to investigate, understand and by contrast to share their findings on the nature of God. In a final section he attempts to reconcile these opposing views.